Rural Hospital Closures: A Scoping Review of Studies Published Between 1990 and 2020 - Planey, Arrianna Marie; Thomas, Sharita R; Friedman, Hannah; Hecht, Hillary K; Kent, Erin; Holmes, G. Mark (Journal of health care for the poor and underserved, 2024)
Between 1990 and 2020, 334 rural hospitals closed in the United States, and since 2011 hospital closures have outnumbered new hospital openings. This scoping review evaluates peer-reviewed studies published since 1990 with a focus on rural hospital closures, synthesizing studies across six themes: 1) health care policy environment, 2) precursors to rural hospital closures, 3) economic impacts, 4) effects of rural hospital closures on access to care, 5) health and community impacts, and 6) definitions of rural hospitals and communities. In the 1990s, rural hospitals that closed were smaller, while rural hospitals that closed in the 2010s tended to have more beds. Many studies of the health impacts of rural hospital closures yielded null findings. However, these studies differed in their definitions of "rural hospital closure." Given the accelerated rate of hospital closures, more attention should be paid to hospitals that serve rural communities of color and low-income communities.